Rapid Recovery Gene Downregulation during Excess-Light Stress and Recovery in Arabidopsis. Issue 8 (13th July 2017) - Crisp, Peter A.; Ganguly, Diep R.; Smith, Aaron B.; Murray, Kevin D.; Estavillo, Gonzalo M.; Searle, Iain; Ford, Ethan; Bogdanović, Ozren; Lister, Ryan; Borevitz, Justin O.; Eichten, Steven R.; Pogson, Barry J.
Abstract : Abiotic stress and recovery transcriptomes reveal extremely short RNA half-lives, changes to cotranslational decay, and recovery-specific networks, consistent with active recovery and cellular memory. Abstract: Stress recovery may prove to be a promising approach to increase plant performance and, theoretically, mRNA instability may facilitate faster recovery. Transcriptome (RNA-seq, qPCR, sRNA-seq, and PARE ) and methylome profiling during repeated excess-light stress and recovery was performed at intervals as short as 3 min. We demonstrate that 87% of the stress-upregulated mRNAs analyzed exhibit very rapid recovery. For instance, HSP101 abundance declined 2-fold every 5.1 min. We term this phenomenon rapid recovery gene downregulation (RRGD ), whereby mRNA abundance rapidly decreases promoting transcriptome resetting. Decay constants ( k ) were modeled using two strategies, linear and nonlinear least squares regressions, with the latter accounting for both transcription and degradation. This revealed extremely short half-lives ranging from 2.7 to 60.0 min for 222 genes. Ribosome footprinting using degradome data demonstrated RRGD loci undergo cotranslational decay and identified changes in the ribosome stalling index during stress and recovery. However, small RNAs and 5ʹ-3ʹ RNA decay were not essential for recovery of the transcripts examined, nor were any of the six excess light-associated methylome changes. We observed recovery-specific gene expression networks upon return to favorable conditions and six transcriptional memory types. In summary, rapid transcriptome resetting is reported in the context of active recovery and cellular memory.